Terapi Aktivitas Kelompok (TAK) Melalui Terapi Okupasi Kolase Biji-Bijian pada Lansia di Wisma Pisang PSTW Budi Mulia 2 Cengkareng Jakarta Barat - Munirah; Alfika Safitri; Ridha Auliasyfa Nabillah; Rangga Yudistira; Nur Aulia Fadilah; Nisa Noviana (Pustaka Galeri Mandiri, 2026)
Elderly individuals experience a decline in physical, cognitive, and social functions which leads to decreased activity, creativity, and social interaction. this condition may cause boredom and loneliness if appropriate stimulation is not provided. this activity aimed to improve activity, creativity, and social interaction among the elderly through group activity therapy using an occupational therapy approach with seed collage activities. the method involved implementing group activity therapy for 12 elderly participants at Wisma Pisang PSTW Budi Mulia 2 Cengkareng, West Jakarta, through orientation, working, and termination stages for 30–45 minutes using drawing paper, glue, and seeds such as mung beans and corn. the results showed that most participants were able to follow the activity well, indicated by increased participation, ability to paste seeds according to patterns, and interaction among participants. the activity also had positive effects on improving fine motor skills, concentration, creativity, and psychosocial well-being. obstacles such as motor limitations and difficulty understanding instructions were managed through guidance and motivation from facilitators. in conclusion, group activity therapy through occupational therapy using seed collage activities is effective as a non-pharmacological intervention to improve the quality of life of the elderly